P127 Does it matter how they breathe?—Perceptions in COPD patients when adopting different routes of breathing. (16th November 2010) - Williams, A J; Pitcher, A; Thomas, P; Baker, R
Abstract : Introduction: We have reported that normal subjects prefer nasal breathing (NB) and that the adoption of mouth breathing (MB) is associated with uncomfortable sensations including breathlessness.1 MB may predispose to the perception of breathlessness by dynamically changing chest wall mechanics (CWM), and thus proprioceptive input. This study has been extended to COPD patients in whom airways resistance and dynamic hyperinflation is likely to alter CWM. Method: 20 COPD patients, mean age 71 years (range 47–89), FEV1 mean 0.8 l (range 0.4–2.02 l), whilst at rest (tidal breathing), undertook a 2×2 min cross over exercise during which subjects were requested to note their perceptual experiences when randomly allocated to either NB or, after a break, MB. The results have been compared to the individuals preferred route of breathing normally and 20 normal subjects (controls).1 Results: 10/20 (50%) of COPD patients during NB found the exercise to be uncomfortable compared to only 3/20 (15%) controls (p=0.04). 9/20 (45%) witnessed discomfort with breathing/breathlessness, 0/20 dry mouth and 2/20 (5%) a desire to cough. 13/20 (65%) of COPD patients during MB found the exercise to be uncomfortable compared to 10/20 (50%) controls (p=0.52). 8/20 (40%) COPD patients witnessed discomfort with breathing/breathlessness, and dry mouth 6/20 (30%). 6/20 (30%) COPD patients preferred NB, 7/20 (35%) had no preference and 7/20 (35%) preferred MB during normal breathing in usual life. This compares to 13/20 (65%), 4/20 (20%) and 3/20 (15%) respectively for controls. 9/20 (45%) COPD patients had a positive Nijmegen score (>23) (compared to 0/20 controls) and Hospital Anxiety Depression (HAD) scores were greater in COPD (p<0.001). Depression in COPD patients was strongly associated with a preference for MB normally (r=0.6, p=0.007). Conclusions: This study has shown that COPD patients, in contrast to controls, have adopted a shift in breathing preferences to favour MB. High scores for Nijmegen and HAD in COPD suggest ventilatory dysfunction with depression closely linked to MB. We hypothesise that MB in COPD patients is intricately linked to high levels of ventilatory dysfunction and depression.